Association Between the Systemic Inflammation Response Index and Severity of Acute Pancreatitis: A Retrospective Cohort Study - Wu W; Zhang Y; Zhang Y; Qu X; Zhang Z; Zhang R (Journal of Inflammation Research)
Wen Wu,1,2 Yupei Zhang,1,2 Yilan Zhang,1,2 Xingguang Qu,1,2 Zhaohui Zhang,1,2 Rong Zhang1,2 1Department of Emergency and Critical Care Medicine, Yichang Central People’s Hospital, Yichang, Hubei, 443003, People’s Republic of China; 2The First College of Clinical Medical Science, China Three Gorges University, Yichang, Hubei, 443003, People’s Republic of ChinaCorrespondence: Rong Zhang, Department of Emergency and Critical Care Medicine, Yichang Central People’s Hospital, The First College of Clinical Medical Science of China Three Gorges University, Yichang, Hubei, 443003, People’s Republic of China, Tel/Fax +86-0717-6481546, Email zhangrong20240304@163.comPurpose: This study aimed to determine the association of the systemic inflammatory response index (SIRI) with severity in patients with acute pancreatitis (AP).Methods: This retrospective study was conducted using clinical data of 1514 patients with AP who were admitted between January 2019 and October 2023 to the First Clinical Medical College of Three Gorges University. SIRI was calculated as peripheral blood neutrophils × monocytes/lymphocytes ratio, and patients were divided into tertiles according to the SIRI levels. The comparison of demographic characteristics, clinical manifestations, laboratory parameters, and outcomes was made among groups. We also carried out multivariate logistic regression to analyze risk factors independently and forecast AP severity. Furthermore, the relationship between SIRI and AP severity was assessed using restricted cubic spline analysis. Subgroup analysis was conducted according to age, sex, body mass index, diabetes, white blood cell count, sequential organ failure assessment score, requirement for continuous renal replacement therapy, and etiology of AP.Results: Among the 1514 enrolled patients, 171 (11.3%) developed severe AP. Higher SIRI levels were independently related to the higher incidence of severe AP (adjusted P < 0.05) after adjusting the possible confounders. Nonlinear curve fitting demonstrated the reverse J-shaped relationship of SIRI with AP severity, with inflection points at 13. A consistent association was observed across various subgroup analyses.Conclusion: SIRI independently forecasts the severity of AP. This readily available biomarker may facilitate early stratification of risk and prompt intervention in clinical practice.Keywords: acute pancreatitis, systemic inflammatory response index, severity